Interface-enforced complexation between copolymer blocks1. Issue 18 (14th May 2015) - Steinschulte, Alexander A.; Xu, Weinan; Draber, Fabian; Hebbeker, Pascal; Jung, Andre; Bogdanovski, Dimitri; Schneider, Stefanie; Tsukruk, Vladimir V.; Plamper, Felix A.
<x xml:space="preserve">Abstract</x> If they do not meet in 3D, arrange an encounter in 2D: weakly attracting poly(propylene oxide) and poly(dimethylaminoethyl methacrylate) complex at the interface, while in bulk water hardly any interaction can be detected.